Design and control of a 6-degree-of-freedom precision positioning system. (April 2017) - Cai, Kunhai; Tian, Yanling; Wang, Fujun; Zhang, Dawei; Liu, Xianping; Shirinzadeh, Bijan
Abstract: This paper presents the design and test of a 6-degree-of-freedom(DOF) precision positioning system, which is assembled by two different 3-DOF precision positioning stages each driven by three piezoelectric actuators (PEAs). Based on the precision PEAs and flexure hinge mechanisms, high precision motion is obtained. The design methodology and kinematic characteristics of the 6-DOF positioning system are investigated. According to an effective kinematic model, the transformation matrices are obtained, which is used to predict the relationship between the output displacement from the system arrangement and the amount of PEAs expansion. In addition, the static and dynamic characteristics of the 6-DOF system have been evaluated by finite element method (FEM) simulation and experiments. The design structure provides a high dynamic bandwidth with the first natural frequency of 586.3 Hz. Decoupling control is proposed to solve the existing coupling motion of the 6-DOF system. Meanwhile, in order to compensate for the hysteresis of PEAs, the inverse Bouc-Wen model was applied as a feedforward hysteresis compensator in the feedforward/feedback hybrid control method. Finally, extensive experiments were performed to verify the tracking performance of the developed mechanism. Highlights: Design of a 6-degree-of-freedom (DOF) precision positioning system. According to an effective kinematic model, the transformation matrices are obtained. The inverse Bouc-Wen model was applied as a feedforward hysteresis compensator. Extensive experiments were performed to verify the good tracking performances.